2023
DOI: 10.1002/ldr.4652
|View full text |Cite
|
Sign up to set email alerts
|

Plant α‐and β‐diversity, and soil microbial stoichiometry co‐regulate the alterations in ecosystem multifunctionality in response to grazing and N addition in a typical steppe

Abstract: Despite their significance, how interactions of plant diversity at multiple spatial scales and soil microbial stoichiometry alter a series of ecosystem functions (multifunctionality, EMF) in response to anthropogenic nitrogen (N) input and herbivores are poorly known. We conducted a 17-year sheep grazing experiment with 6-year N addition to explore the impacts of grazing (0, 2.7, 5.3 and 8.7 sheep ha À1 ) and N addition (N0, N5, N10 and N20, i.e., 0, 5, 10 and 20 g N m À2 yr À1 , respectively) on grassland fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Several studies showed that grazing‐induced plants stimulated growth rates to compensate for the lost issues (Li et al, 2023). Annual crop increased aboveground biomass after grazing (Figure 3) and induced compensatory growth of photosynthetic shoots to cover the high plant C costs (Sun et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that grazing‐induced plants stimulated growth rates to compensate for the lost issues (Li et al, 2023). Annual crop increased aboveground biomass after grazing (Figure 3) and induced compensatory growth of photosynthetic shoots to cover the high plant C costs (Sun et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Grazing is one of the most important usages of grassland ecosystems (Li et al, 2023). Understanding the effects of grazing on soil N mineralization and cycling of ecosystems can help in improving grassland management and predicting climate‐biosphere feedback (He et al, 2020; Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%